Social Media and the Costs of Distraction: Neurobiological Perspectives on the Quality of Life - Ellingsen, Mark (Journal of interdisciplinary studies, 2021)
There are well-known studies about how heavy use of social media is not conducive to happiness. Although poll data are mixed on this matter, one should be especially cautious in view of the apparent promise of internet connectedness. This essay examines recent research in neurobiology on what social media seems to be doing to human brains. It explores how regular social media use scatters concentration because the prefrontal cortex is not activated. This has negative implications for long-term and working memory. Even more problematic, the less use of the prefrontal cortex the less likely we are to exhibit empathetic, emotional maturity, love, and live with a sense of the transcendent. As with every advance in human technology, one needs to begin using social media with realistic expectations, ever seeking to safeguard from potential abuses associated with it. The essay concludes with a call for moderation and balance in use of the internet, with a Biblically-based, scientific plea not to overlook those activities which activate all parts of the brain, which with heavy internet use can be allowed to atrophy. Balance is shown to be the key to the quality of life.